A study on the histological changes in infected gold fish (Carrassius auratus auratus) by the parasitic fungus Saprolegnia parasitica in vitro - Sana Q. Badr; Al- Duboon, Abdul-Hafiz; Muhsin, Tawfek M. (Iraqi Journal of Aquaculture, 2022)
The ornamental fish, Carrassius auratus auratus was artificially infected by the water mold Saprolegnia parasitica. The infected fishes were left in aquariums without treatment until they died for purpose of histological study. Skin and muscle tissues sections have been prepared and stained by PAS. The results showed clear tissue changes represented by erosion and necrosis of the skin epidermis and muscles.